Effects of the UV-filter Oxybenzone on estrogen and testosterone levels in adult Zebrafish (Danio rerio) (Texas Journal of Agriculture and Biological Sciences, 2024)
The usage of sunscreens has become integral in daily skincare routines due to their role in preventing sunburns and reducing the risk of skin cancer. One type of sunscreens is chemical sunscreens, encompassing compounds like Oxybenzone, which absorb and convert UV radiation. While Oxybenzone is recognized for its efficacy in UV protection, concerns regarding its safety have emerged. Furthermore, research suggests Oxybenzone may be a hormone disruptor, potentially affecting aquatic ecosystems and organisms like Zebrafish (Danio rerio). This study aimed to investigate the effects of acute exposure to Oxybenzone on hormone levels, specifically estrogen (17-beta estradiol) and testosterone, in adult Zebrafish. Significant alterations in hormone concentrations were observed through controlled exposure experiments. Testosterone levels were notably reduced in fish exposed to Oxybenzone, while 17-beta-estradiol concentrations increased, indicating potential endocrine-disrupting effects. The findings underscore the importance of understanding the ecological implications of sunscreen ingredients beyond their intended human benefits. Further research is warranted to elucidate the broader impact of Oxybenzone on aquatic environments and wildlife, guiding regulatory measures and public awareness efforts to mitigate potential harm